PENGARUH PENEMPATAN PEGAWAI, BEBAN KERJA, DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA BANTUL - Nur Widiastuti; Alex Taufiq (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Human resources is an organizational asset that should be managed properly, especially regarding placement, assignment of workloads, and career development for the employees. Proper human resources management, hopefully, will improve organizational performance therefore set results. This study aims to determine the influence the placement and workload of employees unto their performance. This study will use quantitative research method with non-probability sampling method. The respondents in this study originated from KPP Pratama Bantul, totaling 91 employees. The sampling technique used is census sample, by distributing questionnaires. The results of the study revealed that employee placement, workload, and career development all partially and simultaneously have a positive and significant effect on employee performance.